Implementation of a Novel model to enhance Routine HIV care and Treatment capacity in South Africa: Outcomes, Costs, and Cost-effectiveness - Navario, Peter Scott (School of Economics, 2014)
Introduction: This research evaluated the implementation of a novel public-private partnership (PPP) between the provincial department of health, an NGO, and a local private sector general practitioner (GP) network, which provides routine HIV care and treatment to public sector patients in order to alleviate the patient burden at public sector primary care clinics. Methods: This was a retrospective cohort study that compared the PPP model to the status quo public primary healthcare clinic (PHC) model in terms of patient outcomes, costs and cost-effectiveness. Outcomes data (viral suppression, patient retention and other clinical outcomes) were collected from clinic records and patient files. Cost data included HIV and TB treatment, laboratory tests, down-referral care, and hospital-based outpatient and inpatient care. In addition, a new program performance metric proposed a cost associated with premature treatment attrition. Total and average costs for each model were based on resource utilization. Average cost and incremental cost per patient retained, cost per suppressed patient, and cost per suppressed patient remaining in down-referral care were calculated. Finally, a survey was conducted with a sub-set of study patients in order to incorporate patient experience and perceptions of each care model into the analysis. Results: The proportion of patients who remained in care at the down-referral site with suppressed viral loads was 83 and 55 percent in the PPP and PHC cohorts respectively. Eighty-eight percent of PPP patients had suppressed viral loads compared to 67 percent of PHC patients. Retention on treatment was 94 percent among PPP subjects and 75 percent among PHC subjects. Total model cost was higher in the PPP model (R2,153,233) compared to the PHC model (R1,556,591) during the study period. The average cost per suppressed patient in down-referral care was R646.41 per month in the PPP model and R724.00 per month in the PHC model, and the cost per patient retained was R570.85 in the PPP model and R516.45 in the PHC model. The incremental cost-effectiveness ratio (ICER) was R724.00 for the PHC model and R505.20 for the PPP model compared to a 'do nothing' alternative. The PHC model was dominated (extended dominance), and the ICER for the PPP model compared to a 'do nothing' alternative was R638.97. Discussion: Despite recent progress in scaling-up HIV services in South Africa, an intensified effort will be required to meet the rapidly growing demand for treatment over ii the next decade. A lack of human resources has been identified by experts as one of the biggest constraints to achieving further scale-up of ART. The PPP model evaluated here was designed to help alleviate some of the pressure on the public health system by utilizing local private sector GPs to provide routine care for treatment experienced patients in Matlosana, North West Province. Clinical outcomes in the PPP model were significantly better than in the PHC model, it was more cost-effective at producing virally suppressed patients in down-referral care, and PPP patients were equally as happy as PHC patients with the quality of care and the level of convenience that the model offered. Innovative partnerships like the one evaluated here may offer a strategy for boosting public health sector capacity by leveraging existing private sector health resources.